The Business of Tourism / Fourth Edition - Holloway Christopher J (Longman, 1994)
A basic understanding of the nature, structure and organization of the tourist industry. Preface, An Introduction to Tourism, The History of Tourism: From Its Origins to the Age of Steam, Tourism in the Twentieth Century, The Economics of Tourism, Tourist Motivation and Behavior, The Structure and Organization of the Travel and Tourism Industry, Passenger Transport: The Aviation Business, Water-Borne Passenger Transport, Rail and Road Passenger Transport, The Hospitality Sector: Accommodation and Catering Services, Visitor Attractions and Visitor Management, Tour Operating, Travel Retailing, Ancillary Tourism Services, The Structure and Role of Public Sector Tourism, Tourism Design and Management, The Social and Environmental Impact of Tourism, Bibliography, Index.